Development of Social Media Online Education Communication Strategy in Jean Mayer Preschool - Jenni Florida Tambunan; Rachmat Kriyantono; Bambang Dwi Prasetyo (International Journal of Science and Society, 2021)
Since the end of 2019, the dynamics of global life have been shaken by the Covid-19 pandemic. The Covid-19 pandemic has also caused multi-sectoral impacts on various areas of human life, one of which has an impact on the field of education. This study aims to determine the marketing communication strategy carried out by Jean Mayer Preschool to continue to exist in the pandemic era. This research is a type of qualitative research. The focus of this research is to find out the educational services promotion strategy at Jean Mayer Preschool. The data collection technique in this research is interview. Data analysis technique is through Miles, Huberman, Saldana. The results showed that the marketing strategy for educational services after the pandemic during the distance education (PJJ) was to use social media for the promotion of montessori activities and English language habituation. The method used is Home Based Learning, Video Watching Learning, Home Visit Learning. The social media used are Facebook, Instagram, and WhatsApp. The digital marketing strategies used include selecting photos, videos, and writing captions to promote Jean Mayer preschool. Social media is used effectively as the actualization of digital marketing in order to maintain communication and improve the quality of distance learning (PJJ) between teachers, students and parents of students.